Efektivitas Ekstrak Myristica fragrans Houtt Terhadap Bakteri Patogen Pseudomonas aeruginosa dan Methicilin Resistensi Staphylococcus aureus - Pramita Wally; Andi Sitti Marwah; Azril Fajar Warang (Jurnal Biotek, 2022)
Nutmeg (Myristica fragrans Houtt) is enriched with secondary metabolites and has been traditionally believed to be useful in the treatment of infection and inflammation. The aim of this study was to determine the effective concentration of nutmeg extract in inhibiting skin pathogenic bacteria Pseudomonas aeruginosa and Methicillin-Resistant Staphylococcus aureus (MRSA). The research type was a laboratory experiment to measure antibacterial activity in vitro through Kirby and Bauer's disk diffusion technique. Work procedures included a phytochemical test, extraction, and antibacterial activity tests. The results of the study based on the one-way ANOVA test showed that f-count ˃ f-table which means that nutmeg pulp extract was effective in inhibiting P. aeruginosa and Meticillin Resistance of Staphylococcus aureus as a whole total treatment. The concentration of 80% was the highest concentration, with an average diameter of the inhibition zone against P. aeruginosa of 17.3 mm and 19.6 mm for the inhibition zone of Meticillin-Resistant Staphylococcus aureus. The mean value of the diameter of the inhibition zone is categorized as a strong antibacterial substance.